ANALYSIS OF READING INTEREST OF ENGLISH LANGUAGE EDUCATION STUDENTS IN SEMESTER 6 (SIX) OF THE UNIVERSITY OF MUHAMMADIYAH BENGKULU ON SCINTIFIC ARTICLES - Uswatun Hasanah; Derry Ellis Novela Bustam; Ivan Achmad Nurcholis (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2023)
Reading is a positive activity that has a myriad of benefits to increase knowledge and insight. According to Santoso (2011) in reading there are 2 aspects that need to be considered, namely interest (a combination of desire, willingness and motivation) and reading skills, namely eye skills and mastery of reading techniques with the goal of realizing efficient reading habits. reading problems occur in Indonesia due to a lack of active interest in reading, UNECSO notes that Inodenesia's reading interest ranks 60th out of 61 countries. This shows how low the reading interest of Indonesian people is. With this problem, the author conducted research on the reading interest of journals / scientific articles of 6th semester students of the English Education Study Program, Universitas Muhammadiyah Bengkulu. This study aims to determine and identify the interest of FKIP English Education students at Muhammadiyah Bengkulu University in reading scientific articles, especially journals. In this study the author used descriptive method, in collecting data the author used a questionnaire. the subject of this research is 6th semester FKIP English students, based on the results of the analysis that has been done by the author, it is found that 6th semester students of English Education Study Program at Universitas Muhammadiyah Bengkulu have a low interest in reading scientific articles. In addition to interest in reading articles, in this study the authors also found that students not only read journals and scientific articles from their majors, but also like to read scientific writings from other fields besides their majors.